Groundwater Quality Characterization for Safe Drinking Water Supply in Sheikhpura District of Bihar, India: A Geospatial Approach - Kumar, Ritesh; Singh, Sarnam; Kumar, Rakesh; Sharma, Prabhakar (Frontiers in Water, 2022)
Groundwater quality due to geogenic factors, aggravated by anthropogenic activities, is a significant threat to human well-being and agricultural practices. Groundwater quality parameters of fluoride, iron, total dissolved solids, and pH were analyzed using the Kriging interpolation technique in the GIS domain for in-situ observations of 206 wells and bore wells in Sheikhpura district, Bihar. Each of the modeled geospatial maps was validated using a set of 17 in-situ observations. The best fit model between observed and predicted variables such as fluoride, iron, total dissolved solids, and pH produced a coefficient of determination (R2) of 0.96, 0.905, 0.91, and 0.906, respectively. The analysis indicated that the periphery south of Chewara and Ariari blocks, i.e., about 9.16% of district area, is affected by fluoride concentration (1.55-2.32 mg/l) which is highly unsuitable for consumption, whereas, remaining area (90.84%) is within the permissible limit of fluoride concentration (0.37-1.54 mg/l). In most areas, iron concentration is beyond permissible limits (>0.1 mg/l), except 3.10% area in the eastern region with 0.06-0.12 mg/l concentration. However, pH and total dissolved solids were within permissible limits. The study provides insights and understanding on the groundwater pollution regimes and will be helpful to policymakers for better planning, investments, and management to supply potable water in the area.